2016
DOI: 10.1016/j.neuroscience.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Anabolic steroids alter the physiological activity of aggression circuits in the lateral anterior hypothalamus

Abstract: Syrian hamsters exposed to anabolic/androgenic steroids (AAS) during adolescence consistently show increased aggressive behavior across studies. Although the behavioral and anatomical profiles of AAS-induced alterations have been well characterized, there is a lack of data describing physiological changes that accompany these alterations. For instance, behavioral pharmacology and neuroanatomical studies show that AAS-induced changes in the vasopressin (AVP) neural system within the latero-anterior hypothalamus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…The adolescent brain, still in development, is more susceptible to negative effects of anabolic androgenic steroid use (Lumia & Mcginnis, ; for review, see Clark & Henderson, ), which can change cell types and activity patterns within the hypothalamus (Morrison, Sikes, & Melloni, ). The adolescent brain is primed for steroid‐dependent changes; thus, changes may occur which would not be seen in adult users (Henderson et al, ).…”
Section: Psychiatric Effectsmentioning
confidence: 99%
“…The adolescent brain, still in development, is more susceptible to negative effects of anabolic androgenic steroid use (Lumia & Mcginnis, ; for review, see Clark & Henderson, ), which can change cell types and activity patterns within the hypothalamus (Morrison, Sikes, & Melloni, ). The adolescent brain is primed for steroid‐dependent changes; thus, changes may occur which would not be seen in adult users (Henderson et al, ).…”
Section: Psychiatric Effectsmentioning
confidence: 99%
“…Other drugs that can induce AB are antihistamines, statins, and anabolic steroids [154156]. In children, second-generation antihistamines can produce aggression, agitation, and hyperactivity [154].…”
Section: Other Potential Mechanismsmentioning
confidence: 99%
“…It is not surprising that AB is a common adverse reaction to anabolic-androgenic steroids (AAS) [133, 156, 157]. Studies have shown that AAS not only increase AB temporarily, but also may lead to psychiatric long-term consequences as their use in or close to puberty may induce permanent changes in the developing brain [133, 156, 157]. AAS has been shown to modify the expression of cerebral androgen, GABA A , and DA receptors, as well as affect the 5-HT system and the levels of neuroactive substances, e.g., vasopressin, substance P, and stress hormones [133].…”
Section: Other Potential Mechanismsmentioning
confidence: 99%
“…In addition to these neurotransmitter effects, vasopressin is known to be a key modulator of androgen effects by directing androgen action in the hypothalamus to coordinate outward aggression or threat avoidance/anxiety (Morrison et al, 2016a ). Synthetic androgens affect the firing of these vasopressin neurons via indirect effects on serotonergic and dopaminergic pathways within this circuit (Morrison et al, 2016b ). Prefrontal—amygdala signaling neurons are also affected via suppression of serotonergic tone (Ambar and Chiavegatto, 2009 ), suggesting a primary impact on prefrontal—limbic control of behavior in response to salient emotional or rewarding stimuli.…”
Section: General Brain Arousal and Androgen Effects On Central Nervoumentioning
confidence: 99%